A CASE OF SPHENOID SINUS MUCOCELE FOLLOWING ENDOSCOPIC SINUS SURGERY FOR FUNGAL SINUSITIS - B., Satheesh Kumar Bhandary; Bhat, Vadisha Srinivas (Journal of Health and Allied Sciences NU, 2013)
Paranasal sinus mucoceles are common in frontal sinus, followed by ethmoid and maxillary sinuses. Sphenoid sinus is the least common site of mucocele, representing less than 2% of all paranasal sinus mucoceles. Here we present a case of sphenoid sinus mucocele, developing in a patient, who underwent endoscopic sinus surgery for fungal sinusitis involving the sphenoid sinus, presented with headache as the only complaint. The mucocele was diagnosed radiologically and was treated surgically by endoscopic sinus surgery.
Keywords: Mucocele; Sphenoid sinus; Fungal sinusitis; Headache; Endoscopic sinus surgery